Risks of excessive screen use. Digital detox strategies - Trejo Espíndola, Leticia (Mexican Journal of Medical Research ICSA, 2025)
We often dedicate our routines to screen time, enjoying the benefits and entertainment that screen time provides, however, it is also necessary to consider the impact and consequences of excessive screen time. The objective of this research focuses on: a) identifying the consequences of excessive screen time, such as increased obesity, sleep disorders, depression, anxiety, behavioral problems, and isolation; and b) providing digital detox options that are possible to carry out, setting limits on their use, which allows for more affectionate and warm relationships, in addition to taking advantage of time in activities that promote physical activity that benefit personal well-being.